2017
DOI: 10.1080/14786419.2017.1290622
|View full text |Cite
|
Sign up to set email alerts
|

A new xanthone from the fungusApiospora montagnei

Abstract: A new xanthone derivative, methyl 8-hydroxy-3-hydroxymethylxanthone-1-carboxylate (1), and seven known compounds, 8-hydroxy-3-methylxanthone-1-carboxylate (2), methyl 8-hydroxy-6-methylxanthone-1-carboxylate (3), ergosterol (4), cyathisterone (5), ergosta-4,6,8(14),22-tetraen-3-one (6), calvasterone (7) and 2-hexyl-3-methylmaleic anhydride (8) were first isolated from the fungus Apiospora montagnei. Their structures were elucidated on the basis of spectroscopic analysis (UV, IR, MS, 1D, and 2D NMR). Compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…by Yang et al showed cytotoxicity against HepG2 and HEp-2 cells (IC 50 = 30 and 26.7 µM, respectively) [59]. At the same time, closely related conioxanthone A from Penicillium citrinum did not demonstrate toxicity to KB, MCF-7, and NCI-H137 cell lines [56]. In Table 6, we summarized yields and properties of 1-13.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…by Yang et al showed cytotoxicity against HepG2 and HEp-2 cells (IC 50 = 30 and 26.7 µM, respectively) [59]. At the same time, closely related conioxanthone A from Penicillium citrinum did not demonstrate toxicity to KB, MCF-7, and NCI-H137 cell lines [56]. In Table 6, we summarized yields and properties of 1-13.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, compound 1 differs from other described xanthones by location of methyl group at C-3 instead of C-6. An example of such xanthone derivatives is 8-hydroxy-3-methylxanthone-1-carboxylate from Apiospora montagnei [56]. Therefore, 1 was suggested to be derived from chrysophanol [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation